2022
DOI: 10.1038/s41467-022-30794-7
|View full text |Cite
|
Sign up to set email alerts
|

RNF43 G659fs is an oncogenic colorectal cancer mutation and sensitizes tumor cells to PI3K/mTOR inhibition

Abstract: The RNF43_p.G659fs mutation occurs frequently in colorectal cancer, but its function remains poorly understood and there are no specific therapies directed against this alteration. In this study, we find that RNF43_p.G659fs promotes cell growth independent of Wnt signaling. We perform a drug repurposing library screen and discover that cells with RNF43_p.G659 mutations are selectively killed by inhibition of PI3K signaling. PI3K/mTOR inhibitors yield promising antitumor activity in RNF43659mut isogenic cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Figure 5C shows the detailed list of high-frequency interaction genes in cancer and normal samples. Previous studies demonstrated that abnormal expression of HOXD11 promotes the malignant behavior of glioma cells ( 78 , 79 ). Our results indicate that HOXD11 is a specific high-frequency interaction gene in glioma (Figure 5C ), and there are obvious chromatin interactions between an enhancer enrichment region and the gene HOXD11 in glioma (Figure 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5C shows the detailed list of high-frequency interaction genes in cancer and normal samples. Previous studies demonstrated that abnormal expression of HOXD11 promotes the malignant behavior of glioma cells ( 78 , 79 ). Our results indicate that HOXD11 is a specific high-frequency interaction gene in glioma (Figure 5C ), and there are obvious chromatin interactions between an enhancer enrichment region and the gene HOXD11 in glioma (Figure 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidence highlights the pivotal role of RING-type E3 ligases and their substrates in a wide range of human diseases and mutation of RING-type E3s, or modulation of their activity is frequently associated with pathogenesis including viral infections, neurodegenerative disorders, autoimmune diseases and cancer (Cai et al, 2022; Chen et al, 2022; Duan and Pagano, 2021). Indeed, RNF43 mutations have been associated with aggressive tumor biology such as colorectal and endometrial cancer (Fang et al, 2022; Matsumoto et al, 2020; van Herwaarden et al, 2021). To evaluate the impact of other PA-TM-RING E3 ligases in cancer we analyzed TCGA (The Cancer Genome Atlas) tissue mRNA expression data obtained for RNF128, RNF130, RNF167, RNF43 and ZNRF3 from 17 cancer types representing 21 cancer subtypes.…”
Section: Mainmentioning
confidence: 99%
“…While we reveal a key role of adjustable WNT signalling for TINC formation and BRAF / RNF43 -mutant tumour survival and growth, additional pathways may play a role. RNF43 truncating mutations were recently linked to activation of the PI3K-Akt-mTOR pathway 37 , which also mediates activation of cellular programs linked to glycolysis and hypoxia 38 , as well as Goblet and Paneth cell differentiation in the mouse intestine and human intestinal organoids 22,23,39,40 . Our findings further indicate that the cancer driver activity of WNT mutations relies on a specific mutational context.…”
Section: Mainmentioning
confidence: 99%